FAKTOR YANG MEMPENGARUHI KEBIJAKAN UTANG PADA PERUSAHAAN MANUFAKTUR DI BEI - Sunandy, Jonathan Alvin; Sha, Thio Lie (Jurnal Paradigma Akuntansi, 2024)
This study aims to obtain empirical evidence regarding the effect of structure asset, firm size, dividend policy, and profitability on the firm debt in manufacturing companies on the IDX. The technique sampling used was purposive sampling. The company data in the study were 30 companies. This study uses secondary data that is processed using Eviews version 12. The F test show that structure asset, firm size, dividend policy, and profitability have a significant effect on debt policy. The t test show that profitability has a positive significant effect on debt policy, structure asset has a negative insignificant effect on debt policy. Firm size and dividend policy have a positive insignificant effect on debt policy. The implication of this study is to provide consideration in making decisions for companies related to factors that affect debt policy.